Financial Cost Allocations: A Game-Theoretic Approach. - Callen, Jeffrey L. (The Accounting Review, 1978)
Arthur L. Thomas has argued that financial cost allocations in general and depreciation allocations in particular are arbitrary and incorrigible whenever the firm's revenues are generated by interacting assets. The game-theoretic Shapley technique is applied to the net-revenue-contributions approach to depreciation allocations. The resulting allocations, it is maintained, are non-arbitrary and corrigible if statement users and the accounting profession are willing to accept a constitution of three "reasonable" allocation axioms.